Consolidação do Núcleo de Inovação Tecnológica: estudo de caso da Universidade Federal de Roraima - Pereira, Sammy Aquino (2019)
Universities are the main promoters of basic and applied knowledge. However, there is still a difficulty in the transition of knowledge, mainly applied, that generated products, processes, improvements and others, for the market and the generation of innovation, when it is accepted in society. In this way, the Law of Innovation, the creation of sectors that would manage this knowledge and identify these technologies in each Scientific, Technological and Innovation Institution was determined by means of Law 10973/2004, in the case of Universities, these sectors were denominated Nuclei of Technological Innovation (NIT). However, the structuring of NITs is still fragile and lacking good practices in several parts of the country. In this sense, the objective of this work was to map the NIT / UFRR implementation situation, identifying its guidelines and performance bottlenecks, that at the end of the research one could present a proposal to consolidate the NIT as a unit effectively responsible for the management of intellectual property and innovation of the Federal University of Roraima, through the elaboration of regulations to meet its attributions. To achieve this goal, the methodology used was the case study, with the mapping of the NIT performance, through semi-structured interviews divided into evaluation axes; as well as using a situational diagnosis. Secondly, a benchmarking was carried out with three institutions and elaboration of a proposal for Consolidation of the NIT of UFRR. As a result, we present a Innovation Policy of the UFRR, the Internal Regulations of the NIT, a Model of invention announcement and Intellectual Property Primer of the NIT, so that these normative instruments can subsidize the full efficiency of the NIT.